A beginner’s guide to the Fourth Industrial Revolution in Africa - Abel Matheba (The Thinker, 2019)
A revolution is change that happens over a length of time. This type of change is driven by human beings. It starts as an idea in the minds of a few, and then spreads out into the minds of more people so that it gains momentum to force a change in the world. A political revolution is often forced through protests or policies, where the majority of the affected people drive this change in their desired direction. An industrial revolution is a change in economic power, where the main driver of the economy is changed from a certain technological sector to another.